Health and human rights are inextricably linked in the COVID-19 response. Issue 9 (16th September 2020) - Sekalala, Sharifah; Forman, Lisa; Habibi, Roojin; Meier, Benjamin Mason
Abstract : To mitigate the spread of COVID-19, governments throughout the world have introduced emergency measures that constrain individual freedoms, social and economic rights and global solidarity. These regulatory measures have closed schools, workplaces and transit systems, cancelled public gatherings, introduced mandatory home confinement and deployed large-scale electronic surveillance. In doing so, human rights obligations are rarely addressed, despite how significantly they are impacted by the pandemic response. The norms and principles of human rights should guide government responses to COVID-19, with these rights strengthening the public health response to COVID-19.